Investigation Of Efficiency In Granulation Device (Eurasian Journal of Humanities and Social Sciences, 2025)
This article presents the results of an experiment aimed at improving the efficiency of the granulation process. The study evaluates the impact of one of the key parameters of the granulation device-the number of rollers and the installation angle of the blade-on the quality and physical properties of granules. The results show that an increase in the number of rollers improves the uniformity of granule length and reduces disintegration. The optimal blade angle contributes positively to the stability and strength of granules. The best results were achieved at a 180° angle and with three rollers. This research provides a scientific basis for improving granulation technology and increasing efficiency in industrial production processes